Balancing the Private Property Interests of the Foreign Direct Investors and Host States’ Right to Regulate in the Context of Environmental Concerns in the Public Interest - Pathirana, D. (My University, 2012)
Under customary international law it is deep-rooted that either direct expropriations or indirect expropriations of property belonging to foreign direct investors should be accompanied by the compensation owed by the host state within whose territory such investment projects have been operated. At the same time, the customary international law doctrine of police-power obviously recognizes host states’ right to regulate or take other measures substantially disturbing foreign investors’ property interests without a finding of compensable expropriation in certain circumstances, such as public health and safely, antitrust, consumer protection, securities, land planning and environmental protection. Accordingly, in the context of International Investment Law the doctrine of police-power has been employed as the first and the foremost exception to the primary principle which insists the paying compensation in the events of expropriations, if such hosts states’ measures comply with the prerequisites namely, pursue a legitimate purpose, aimed at the general welfare, non-discriminatory and fall within the realm of the state’s general regulatory or administrative powers. Amongst the well-defined grounds which fall within the ambit of the state’s general regulatory powers, environmental regulation has become the most frequent ground that is used by the host states to exercise their regulatory right in the context of Foreign Direct Investments (FDIs) during the past decades since most of the major trends of environmental degradations such as greenhouse gas emissions, deforestation, loss of biodiversity have been driven by increased economic activity, to which FDI is a noteworthy contributor. Nevertheless, certain environmental regulations initiated by the host states have resulted in significant impact on the economic viability of the FDIs by raising project costs or reducing the value of project assets; as a result, such environmental regulations have been determined as compensable regulatory takings, undermining the rationale behind the doctrine of police power. Consequently, preserving equilibrium between private property interests of foreign direct investors and host states’ right to regulate environmental concerns in the public interest within the parameters of International Investment Law has become a controversial issue which was addressed by three different lines of reasoning or approaches which delineate the police-powers exception in three different arbitral awards namely, Compañía del 124 Desarrollo de Santa Elena S.A. v. The Republic of Costa Rica,1Tectemd v. The United Mexican States,2Methanex v. United States of America.3 Being so, the main objective of this paper is to identify and rationalize the most appropriate approach for upholding equilibrium between interests of the foreign direct investors and host states amongst the three different approaches developed by the jurisprudence on regulatory expropriations in the environmental context. Moreover, the significance of adhering to such an appropriate approach in the context of accomplishing a sustainable community is the secondary objective of this research.